2003
DOI: 10.1074/jbc.m213198200
|View full text |Cite
|
Sign up to set email alerts
|

Structures of Argininosuccinate Synthetase in Enzyme-ATP Substrates and Enzyme-AMP Product Forms

Abstract: In prokaryotes, an arginine is synthesized by eight-step reactions (arginine biosynthetic pathway) using glutamate as a starting material (1). The glutamate is converted to ornithine by five-step reactions, and the ornithine then enters into the urea cycle to produce arginine in three-step reactions. Argininosuccinate synthetase (AsS) 1 catalyzes the seventh step of the arginine biosynthesis (the second step of the urea cycle). AsS reversibly catalyzes the adenosine triphosphate (ATP)-dependent condensation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…An ATP molecule was modelled into the nucleotide-binding domain of human argininosuccinate synthetase using the homologous structure from Th. thermophilus (Goto et al, 2003). The distance between the citrulline molecule and the ATP -phosphate is shorter than the corresponding distance in the E. coli enzyme, in which a conformational change brings the two molecules closer upon ATP binding (Lemke & Howell, 2002).…”
Section: Nitrosylationmentioning
confidence: 97%
See 1 more Smart Citation
“…An ATP molecule was modelled into the nucleotide-binding domain of human argininosuccinate synthetase using the homologous structure from Th. thermophilus (Goto et al, 2003). The distance between the citrulline molecule and the ATP -phosphate is shorter than the corresponding distance in the E. coli enzyme, in which a conformational change brings the two molecules closer upon ATP binding (Lemke & Howell, 2002).…”
Section: Nitrosylationmentioning
confidence: 97%
“…The crystal structures of argininosuccinate synthetase from two bacterial species, Escherichia coli (Lemke & Howell, 2001, 2002 and Thermus (Tm.) thermophilus (Goto et al, 2002(Goto et al, , 2003, have previously been reported. In addition, one unpublished apo structure from the bacterium Thermotoga (Tt.)…”
Section: Introductionmentioning
confidence: 99%
“…For example, in NH 3 -dependent NAD + synthetase, a substrate–binding and specificity loop was ordered, juxtaposed to its adenylylated nucleotide intermediate (48). The structures of other family members, such as argininosuccinate synthetase (49) and β-lactam synthetase (50), also suggest that structurally analogous regions of these proteins are responsible for interaction with their respective substrates.…”
Section: Discussionmentioning
confidence: 99%
“…This transformation occurs in a two-step process that exemplifies the third general mechanism of amine transfer in metabolism (after GAT and PLP action) -ligation of the a-amino group of aspartate and then elimination of fumarate, which is recycled via the TCA cycle [147]. Argininosuccinate synthetase is homologous to asparagine synthetase [148] and uses ATP to activate the urea by adenylation [149]; nucleophilic substitution by aspartate produces argininosuccinate. Argininosuccinate lyase, the terminal enzyme of the pathway, is a member of a family of aspartase enzymes that catalyze the elimination of fumarate (which feeds into the TCA cycle) from aspartate and N-aspartyl derivatives [150,151], demonstrating the generality of this two step synthetase/lyase route for the indirect transfer of ammonia -the third general process for transfer of nitrogen between metabolites.…”
Section: Glutamate Family Amino Acids: Proline and Argininementioning
confidence: 99%